169k views
0 votes
How do you simplify (a3b2)2

User Jscharf
by
4.7k points

2 Answers

0 votes

9514 1404 393

Answer:

a⁶b⁴

Explanation:

The relevant rules of exponents are ...

(ab)^c = (a^c)(b^c)

(a^b)^c = a^(bc)

__

These let us simplify the expression as follows:


(a^3b^2)^2=(a^3)^2(b^2)^2=a^(3\cdot2)b^(2\cdot2)=\boxed{a^6b^4}

_____

Additional comment

It might be helpful to remember that an exponent signifies repeated multiplication.

a·a·a = a³ . . . . . . 'a' is a factor 3 times, so the exponent is 3.

Similarly, ...

(a³)² = (a³)·(a³) = (a·a·a)·(a·a·a) = a⁶

User Davidhwang
by
5.0k points
1 vote

Answer:

a^6b^4

Explanation:

(a³b²)²

a^6b^4

User Eugene Gordin
by
4.3k points